1999
DOI: 10.1063/1.479699
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved infrared diode laser spectroscopy of the ν3 band of the jet-cooled Fe(CO)2 radical produced by ultraviolet photolysis of Fe(CO)5

Abstract: The infrared spectrum of the iron dicarbonyl radical Fe(CO)2 produced in a supersonic jet expansion by the excimer laser photolysis of iron pentacarbonyl Fe(CO)5 was observed by time-resolved infrared diode laser spectroscopy. About 170 transitions, each split into one or two fine structure components, were assigned to the ν3 (CO antisymmetric stretch) band of Fe(CO)2. The assignment was greatly facilitated by spectral simplification caused by rotational as well as vibrational cooling in the supersonic jet. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Extensive spectroscopic and kinetic studies have been reported on unsaturated iron carbonyl complexes Fe(CO) n (n ¼ 1 À 4) [1][2][3][4], because they are prototypical examples of transition metal carbonyl radicals M n (CO) m [4][5][6][7][8][9][10][11][12][13][14][15], where M represents a transition metal element. In our previous papers, for example, we have reported the infrared diode laser spectroscopy of the m 1 (C-O stretch) band [1] and the millimeter-wave spectroscopy [2] of the iron monocarbonyl radical (FeCO) generated by the 193 nm ArF excimer laser photolysis of Fe(CO) 5 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Extensive spectroscopic and kinetic studies have been reported on unsaturated iron carbonyl complexes Fe(CO) n (n ¼ 1 À 4) [1][2][3][4], because they are prototypical examples of transition metal carbonyl radicals M n (CO) m [4][5][6][7][8][9][10][11][12][13][14][15], where M represents a transition metal element. In our previous papers, for example, we have reported the infrared diode laser spectroscopy of the m 1 (C-O stretch) band [1] and the millimeter-wave spectroscopy [2] of the iron monocarbonyl radical (FeCO) generated by the 193 nm ArF excimer laser photolysis of Fe(CO) 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The observed spectral lines, split as triplets by the spin-spin interaction, provided a direct evidence for the 3 R À electronic ground state of FeCO to settle the controversy whether the ground electronic state of this radical is 3 R À or 5 R À [16][17][18][19][20][21][22]. We also combined the supersonic jet technique with the diode laser spectroscopy to observe the jet-cooled iron dicarbonyl radical Fe(CO) 2 [3]. Simplification of the spectrum caused by the jet cooling facilitated the assignment of the m 3 (C-O antisymmetric stretch) band spectrum of Fe(CO) 2 , and the missing of lines at alternate J quantum numbers observed in each spin component confirmed that the Fe(CO) 2 radical is linear and symmetric ðD 1h Þ and that the electronic state is of 3 R À g symmetry.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations